COMPARISON OF COMPRESSIVE STRENGTH OFTHE SINGLE CANTILEVER SPRING BY USING ONE AND TWO ROUNDS COIL - Wibowo, Diana; Dwi Kurniawan, Fajar Kusuma; Pangestu, Novilia (FKG Unlam, 2017)
ABSTRACTBackground: Removable orthodontic appliances have been widely used for correcting malocclusion. It has active components to move a tooth, including a single cantilever spring. Single cantilever spring is indicated for correcting a tooth with a mild degree rotation, moving the individual tooth to labial or buccal direction. In orthodontics, in order to shift the tooth is required aintermitten strength, which one of them is by lengthen the wire with coil addition. An activated spring means performing deflection that produces compressive pressure to shift the tooth. Purpose: To compare the compressive strength of the single cantilever spring by using one and two rounds of coil. Methods: This research was a pure experimentation using post test-only with control design, consisted of two treatment groups, those groups are a single cantilever spring using one round coil and two rounds coil and a control group without using coil. The samples of this study use stainless steel wire with diameter of 0.6 mm, each group is deflected by 2 mm based on millimeter paper block. The compressive strength of each group was measured using a Gauge force meter. Results: Average scoring of the compressive strength was 307.17 gr/mm2 for the control group, the treatment group with single cantilever spring using one round coil was 197.83 gr/mm2 and single cantilever spring group using two rounds coil was 117.33 gr/mm2. The results of LSD test showed that there was significant difference between treatment group and control group. Conclusion: It concludes that the addition of the round coils can decrease compressive strength single cantilever spring.Keywords: compressive strength, coil, deflection, single cantilever spring